PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN LOYALITAS TERHADAP KINERJA PEGAWAI PADA POLITEKNIK PENERBANGAN MEDAN - Betia Warassari (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
This research aims to find out the influence jointly or partially between organizational culture, compensation and loyalty to the performance of the Workers at the Politeknik Penerbangan Medan. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Eighty nine workers become the sample of this research. Data analysis technique used is linear regression  which shows that from the three independent variables applied to the regression model (organizational culture, compensation and loyalty). Organizational culture is significant for 0,000 which can be concluded that organizational culture affects performance (hypothesis 1 accepted). Compensation has significant value 0,006which can be concluded that compensation  affects performance (hypothesis 2 accepted). Loyalty variable has significant value 0,013 which means that loyalty influences performance (hypothesis 3 accepted). Research results show that organizational culture, compensation and loyalty all positively influence the performance of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than α (α=0,05). So, it can be said that organizational culture, compensation and loyalty influence positively the performance of the workers. Thus, hypothesis 4 accepted.